Hubungan Pengetahuan dan Sikap Perilaku Remaja dalam Pencegahan Infeksi Saluran Kemih di MTS Negeri 24 Jakarta Timur - Safitri, Ladina (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Urinary tract infections are the most common infections, it can be said that 50-60% of women will suffer from at least one urinary tract infection in their life. Indonesian Dictionary (2021) knowledge is known as something related to learning. Attitude is a person's reaction that is still closed to a stimulus or object. A person's attitude can be positive or negative (Notoatmodjo 2020). To determine the relationship between knowledge and behavioral attitudes of adolescents in preventing urinary tract infections at MTS Negeri 24 East Jakarta. This research uses a quantitative method with a quasi-experimental approach with a Chi-Square test using a design carried out with one group post-test. Using the Total Sampling sampling technique, a pre-test and post-test were then given to determine the relationship between knowledge and behavioral attitudes of adolescents in preventing urinary tract infections at MTS Negeri 24 East Jakarta. There is a relationship between knowledge and behavioral attitudes of adolescents in preventing urinary tract infections at MTS Negeri 24 East Jakarta. There were 90 class VIII female students in this study, with a sample of 47 female students. Based on statistical analysis, it shows that the p-value of adolescent knowledge is 0.023, while the p-value of behavioral attitudes is 0.026, it is concluded that Ha is accepted, which means there is a relationship between knowledge and behavioral attitudes of adolescents in preventing urinary tract infections. The research results show that there is a significant relationship between the level of knowledge and behavioral attitudes of adolescents in preventing urinary tract infections at MTS Negeri 24 East Jakarta. It is hoped that the results of this research can be used as a guide and evaluation for adolescents in preventing urinary tract infections. Keywords: Knowledge, Behavioral Attitudes, Prevention of Urinary Tract Infections  ABSTRAK Infeksi saluran kemih merupakan infeksi yang paling umum terjadi, dapat dikatakan 50-60% wanita akan menderita setidaknya satu kali infeksi saluran kemih dalam hidupnya. Kamus Bahasa Indonesia (2021) pengetahuan dikenal dengan sesuatu yang berkaitan dengan pembelajaran. Sikap merupakan reaksi seseorang yang masih tertutup terhadap suatu rangsangan atau objek. Sikap seseorang bisa positif atau negative (Notoatmodjo 2020). Untuk mengetahui hubungan pengetahuan dan sikap perilaku remaja dalam pencegahan infeksi saluran kemih di MTS Negeri 24 Jakarta Timur.Penelitian ini menggunakan metode kuantitatif dengan pendekatan quasy eksperimen  dengan uji Chi-Square menggunakan rancangan dilakukan dengan one grup post-test. Dengan teknik pengambilan sampel Total Sampling, kemudian diberikan pre-test dan post-test untuk mengetahui hubungan pengetahuan dan sikap perilaku remaja dalam pencegahan infeksi saluran kemih di MTS Negeri 24 Jakarta Timur.Terdapat hubungan pengetahuan dan sikap perilaku remaja dalam pencegahan infeksi saluran kemih di MTS Negeri 24 Jakarta Timur. Tedapat dari populasi dalam penelitian ini 90 siswi kelas VIII, dengan sampel berjumlah 47 siswi. Berdasarkan analisis statistic menunjukkan bahwa nilai p-value pengetahuan remaja 0,023, sedangkan sikap perilaku nilai p-value 0,026, disimpulkan bahwa Ha diterima yang berarti ada hubungan antara pengetahuan dan sikap perilaku remaja dalam pencegahan infeksi saluran kemih. Dari hasil penelitian menunjukkan terdapat hubungan yang signifikan antara tingkat pengetahuan dan sikap perilaku remaja dalam pencegahan infeksi saluran kemih di MTS Negeri 24 Jakarta Timur. Diharapkan hasil penelitian ini dapat dijadikan pedoman serta evaluasi pada remaja dalam pencegahan infeksi saluran kemih. Kata Kunci: Pengetahuan, Sikap Perilaku, Pencegahan Infeksi Saluran Kemih